Soluble Notch ligand and receptor peptides act antagonistically during angiogenesis - Klose, Ralph Sebastian; Augustin, Hellmut; Fischer, Andreas (Cardiovascular research, 2015)
Aims: Notch signalling is essential for blood vessel formation. During angiogenesis, the Notch ligand DLL4 on the leading tip cell activates Notch receptors on the adjacent stalk cells. DLL4-Notch signalling is impaired by the Notch ligand JAG1 in endothelial cells. The Delta/Serrate/Lag2 (DSL) domain of the Notch ligands binds to the EGF-like repeats 11-13 of the Notch receptor. This study aimed to elucidate how soluble proteins containing these short domains interfere with Notch signalling during angiogenesis. Methods and results: Adenoviral vectors were generated to express the DSL domains of DLL1, DLL4, JAG1, and the Notch1 EGF-like repeats 11-13 fused to immunoglobulin-G heavy chain. These soluble ligand peptides inhibited Notch signalling in endothelial cells and this caused hyperbranching in cellular angiogenesis assays and in the neonatal mouse retina. The soluble Notch receptor peptides bound stronger to JAG1 than DLL4 ligands, resulting in increased signalling activity. This led to impaired tip cell formation and less vessel sprouting in the retina. Conclusion: The minimal binding domains of Notch ligands are sufficient to interfere with Notch signalling. The corresponding soluble Notch1 EGF11-13 peptide binds stronger to inhibitory Notch ligands and thereby promotes Notch signalling in endothelial cells.
Gesehen am 12.03.2018